Factors Affecting the Outcomes of Arthroscopically Repaired Traumatic Vertical Longitudinal Medial Meniscal Tears. Issue 6 (23rd June 2017) - Uzun, Erdal; Misir, Abdulhamit; Kizkapan, Turan Bilge; Ozcamdalli, Mustafa; Akkurt, Soner; Guney, Ahmet
Background: Although numerous studies have assessed arthroscopic medial meniscal repairs, few studies have focused on factors affecting outcomes of vertical longitudinal and bucket-handle repairs. Purpose: To evaluate the factors affecting clinical outcomes of arthroscopically repaired traumatic vertical longitudinal and bucket-handle medial meniscal tears. Study Design: Case series; Level of evidence, 4. Methods: A total of 223 patients underwent arthroscopic repair for medial meniscal tears between 2007 and 2012; 140 patients had isolated tears or concurrent anterior cruciate ligament (ACL) reconstruction, and 80 patients (76 men, 4 women; mean age, 29.1 years; range, 18-49 years) had vertical longitudinal tears and were included in the study. Pre- and postoperative functional status was assessed using physical examinations with Lysholm and International Knee Documentation Committee (IKDC) scores. Barrett criteria were used for clinical assessment of meniscal healing, and magnetic resonance imaging (MRI) was used as the radiologic assessment method. The effects of tear location, length, chronicity, and type; suturing technique; concurrent ACL reconstruction; and patient age, sex, and smoking habits were also investigated. Results: The mean follow-up period was 51.2 ± 9.4 months (range, 34-85 months). The mean Lysholm and IKDC scores improved at final follow-up (both P s <.001). According to clinical scores, Barrett criteria, and MRI, failure was noted in 12 patients (15%). There were no significant differences in age, tear length, tear type, concurrent ACL rupture, suturing technique, or location of the meniscal repair between the success and failure groups. Failure rates were higher for red-white zone tears than for red-red zone tears (10/30, 33.3% vs 2/50, 4%; P = .004). Tear chronicity significantly affected failure rates. Early repairs had higher healing rates than late repairs (100% vs 73.4%; P = .008). Failure rates were higher for smokers than for nonsmokers (9/24, 37.5% vs 3/56, 5.3%; P = .008). Conclusion: Peripheral tears and early repairs have better outcomes and patient satisfaction. Smoking adversely affects meniscal healing.